Mediciones de pico y fondo de rayos X - Mijares, José Luis; Danón, Claudio Ariel; Goldstein, J. I.; Newbury, D. E.; Echlin, P.; Joy, D. C.; Romig, A. D.; Jr., Lyman, C. E.; Fiori, C.; Lifshin, E. (Plenum Pres, 1992)
Fil: Mijares, José Luis Comisión Nacional de Energía Atómica; Argentina